The art of modern tapestry Dovecot Studios since 1912 - Cumming, Elizabeth; Weir, David (Lund Humphries in association with Dovcot Studios, 2012)
"Setting out to celebrate, document and discuss the work and role of an international tapestry workshop, Dovecot Studios, since its foundation in Edinburgh in 1912, this ground-breaking publication uniquely explores the artistic value, nature and identity of modern tapestry through images, essays and the commentaries of weavers, artists and patrons. Dovecot Studios has constantly evolved since it was established before the Great War. Initial Arts and Crafts ideals developed into a more proactive engagement with modernism from the 1950s, when designs came from leading British artists such as Graham Sutherland, Henry Moore, Stanley Spencer, Cecil Beaton and John Piper. In the 1960s international ambition partnered a quest for experimentation, as characterised by collaborations with artists such as Eduardo Paolozzi, David Hockney, Robert Motherwell and Louise Nevelson"--Dust jacket.